Pengaruh Motivasi, Insentif Dan Disiplin Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Nubika Jaya - Ijul Miswanto; Novrihan Leily Nasution; Nur’ainun Gulo (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2025)
This research aims to determine and analyze the influence of motivation, incentives, and work discipline on employe work performance at PT. Nubika Jaya. This research uses a quantitative approach with a sample size of 60 respondents. Data collection was carried out by distributing questionnaires to respondents. The data obtained were analyzed using the SPSS version 27 program. The analysis methods used include validity and reliability tests to assess the quality of the research instrument, classical assumption tests as a prerequisite for analysis, and multiple linear regression analysis. Additionally, a t-test was conducted to determine the partial influence of the independent variables, an F-test to determine the simultaneous influence, and the coefficient of determination to measure the extent of the independent variables' contribution to the dependent variable. The research results indicate that motivation, incentives, and work discipline, both partially and simultaneously, have a positive and significant effect on employe work performance, as evidenced by a t-statistic value greater than the t-table value and a significance level less than 0.05.